2020
DOI: 10.1097/md.0000000000018615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture on patients with chronic urinary retention caused by a lower motor neuron lesion

Abstract: Chronic urinary retention (CUR) is defined as a non-painful bladder that remains palpable or percussible after the patient has passed urine. Acupuncture may decrease PVR and improve bladder function in patients with neurogenic CUR. The aim of this study was to preliminarily observe the effectiveness of electroacupuncture (EA) for patients with CUR caused by a lower motor neuron lesion and to provide some therapeutic data for further study. This study was a pilot study of 30 patients with CUR caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…It is reported that acupuncture is effective in improving urodynamic function and various symptoms related to DBD, and thus acupuncture may be a novel form of alternative therapy for the radical treatment of DBD [ 16 ]. Previous studies have also revealed the advantages of acupuncture in the treatment of bladder dysfunction, which includes alleviation of symptoms (improvement of chronic urinary retention and incontinence), improvement in the quality of life of patients, and delayed progression of DBD [ 17 ]. Electroacupuncture (EA) is based on conventional acupuncture treatment, wherein an electric current is passed through a specific electrical device to stimulate the body's acupoints.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that acupuncture is effective in improving urodynamic function and various symptoms related to DBD, and thus acupuncture may be a novel form of alternative therapy for the radical treatment of DBD [ 16 ]. Previous studies have also revealed the advantages of acupuncture in the treatment of bladder dysfunction, which includes alleviation of symptoms (improvement of chronic urinary retention and incontinence), improvement in the quality of life of patients, and delayed progression of DBD [ 17 ]. Electroacupuncture (EA) is based on conventional acupuncture treatment, wherein an electric current is passed through a specific electrical device to stimulate the body's acupoints.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, increasing attention has been paid to the clinical effects and potential mechanisms of Chinese medicine for NB. [ 14 , 25 ] For instance, electroacupuncture has been reported to exhibit an important role in the improvement of micturition reflex after SCI, and in turn accelerating the recovery of the bladder function. [ 26 ] Tanshinone IIA, the active ingredients of Chinese herb “Danshen” ( Salvia miltiorrhiza Bunge ), has been found to improve urodynamic parameters and bladder functional recovery after SCI induced NB by reducing the inflammation and edema of the bladder tissue as well as enhancing spinal cord regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicine has the advantages of diverse methods, extensive experience, and easy operation. As a result, increasing attention has been paid to the clinical effects and potential mechanisms of Chinese medicine for NB [14,25] . For instance, electroacupuncture has been reported to exhibit an important role in the improvement of micturition reflex after SCI, and in turn accelerating the recovery of the bladder function [26] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations